The Effect of Training and Compensation on Work Achievement (Census of Polyester Production Employees at PT. Bineatama Kayone Lestari Tasikmalaya) - Resa Rismayanti; Kusuma Agdhi Rahmawa; Arga Sutrisna (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of training on work performance at PT. Bineatama Kayone Lestari Tasikmalaya in the Polyester Division and to determine the effect of training and compensation on work performance at PT. Bineatama Kayone Lestari Tasikmalaya in the Polyester Division. The sample taken was 120 respondents, the research was conducted by collecting data using a questionnaire data collection technique, then testing the data with multiple linear regression. The results of the study show that training compensation affect work ferpormance at PT. Bineatama Kayone Lestari Tasikmalaya in the Polyester Division Compensation for work performance at PT. Bineatama Kayone Lestari in the Polyester Division. There is an effect of training and compensation on work performance at PT. Bineatama Kayone Lestari Tasikmalaya in the Polyester Division